The Implementation of 'Test of Evaluating " and " Test of Creating" in the Assessment of Learning by EFL Lecturers in Pandemic Era - Yulis Setyowati; Dwi Fita Heriyawati; Deny Kuswahono (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This research aims at analyzing the implementation of a test of evaluating and test of creating as contained in the mid-term test and final test exercises during the era of Covid-19 pandemic by two English Foreign Language Lecturers.  This research uses a descriptive qualitative method with a document analysis approach intended in analyzing the implementation of a test of evaluating and a test of creating as contained in the mid-term test and final test exercises. The source data of this study is the mid-term tests and final tests that were made during the era of the Covid-19 pandemic by two English Foreign Language Lecturers who teach in the English Literature department in a private University in Java. Data collecting technique is done using documentation and observation methods. The data analysis has been done by data coding. Then, the data is identified based on the categorization of level competency based on the Bloom taxonomy, particularly the evaluating and creating competency level. After that, the data will be analyzed and interpreted.  The finding showed that 'test of evaluating' appeared only one item that requires students to review especially criticizing based on the qualitative standard and criteria. Meanwhile, the second finding was 'test of creating' in mid-term and final test patterned on the ability to produce a new thing by implying the processes inside 'creating' that are 'generating, planning, and producing’.  By implicating Bloom's taxonomy, the lecturers are not only assisted but also expanded and sharpened the assessment, so the purpose of learning is not just teaching transfer but also covering all the cognitive processes needed in learning transfer.